Associations of a Healthy Lifestyle Index With the Risks of Endometrial and Ovarian Cancer Among Women in the Women's Health Initiative Study. Issue 2 (8th November 2018) - Arthur, Rhonda; Brasky, Theodore M; Crane, Tracy E; Felix, Ashley S; Kaunitz, Andrew M; Shadyab, Aladdin H; Qi, Lihong; Wassertheil-Smoller, Sylvia; Rohan, Thomas E
Abstract: Lifestyle-related factors influence risk of endometrial and ovarian cancers, but few studies have examined their joint associations with risk of these cancers. Using multivariable Cox regression models, we assessed the association of a healthy lifestyle index (HLI—a composite score (range, 0–20) involving diet, alcohol consumption, physical activity, body mass index, and smoking; higher scores represent healthier behavior) with risk of endometrial and ovarian cancers among 108, 136 postmenopausal women who were recruited in the US Women's Health Initiative study between 1993 and 1998. After a median follow-up of 17.9 years, 1, 435 endometrial cancer cases and 904 ovarian cancer cases had been ascertained. Women in the highest quintile of the HLI score had a lower risk of overall, type I, well-differentiated, moderately differentiated, poorly differentiated, and localized endometrial cancer than those in the lowest quintile (for quintile 5 vs. quintile 1, hazard ratio (HR) = 0.61 (95% CI: 0.51, 0.72), HR = 0.60 (95% CI: 0.49, 0.72), HR = 0.66 (95% CI: 0.46, 0.96), HR = 0.69 (95% CI: 0.52, 0.90), HR = 0.49 (95% CI: 0.34, 0.72), and HR = 0.61 (95% CI: 0.50, 0.74), respectively). The HLI score had a weak positive association with risk of serous ovarian cancer. Our findings underscore the potential importance of a healthy lifestyle in lowering endometrial cancer risk among postmenopausal women.